Pengembangan Model Pembelajaran Innovation Active Debat untuk Meningkatkan Keterampilan Menyampaikan Pendapat Peserta Didik - Sholahuddin, Atoillah; Awaliyah, Siti (Universitas Negeri Malang, 2021)
This study aimed to produce the development of the innovation active debate learning model to improve the skills of expressing students’ opinions. The procedure of the research and development was based on the steps proposed by Borg & Gall. The test subjects in this study were students of Class X Religion B and X Social Studies A Madrasah Aliyah Darun Najah Karangploso. The results showed that the innovation active debate learning model was valid and able to improve the skills of expressing students’ opinions. The post-test results obtained by students were higher than the pre-test results. This showed that there had been a significant change in the skills of expressing students’ opinions before and after the innovative active debate learning model was applied.